The 'Palestine poster' and everyday memoricide: Making killing memory mundane. Issue 3 (November 2021) - Webster, Scott
This article looks at the Liberation Graphics Collection of Palestine Posters – a collection of 1600 'Palestine posters' submitted to UNESCO's Memory of the World programme during its 2014–2015 and 2016–2017 rounds. Despite receiving unanimous support for inscription, this nomination was effectively vetoed twice by UNESCO's Director-General. The Collection frames the Palestine poster as 'an essential medium through which Palestinians communicated their aspirations and international supporters expressed their solidarity'. Among these aspirations is a desire to identify and expose Israeli memoricide ('the killing of memory'). Importantly, symbols like the house-key and olive tree transform otherwise mundane objects into potent signifiers calling attention to how memoricidal processes impacted spaces beyond the high-profile. Conversely, by drawing upon Zionist posters collected within the more expansive Palestine Poster Project Archives online, my analysis also explores the reconstructive side of memoricide. These materials simultaneously facilitate and obfuscate the killing of memory. Memoricide becomes normalised, a mundane (and thus invisible) facet of everyday life, practised by ordinary people.